Mid-Term Appraisal of Ninth Five Year Plan 1997-2002 Government of Punjab - Planning Commission (Planning Commission, 1997)
The Planning Commission had approved an outlay of Rs.14300.00 crores at current prices (Rs.11500.00 crores at constant prices) for the 9th Five Year Plan (1997-02)of the State marking an increase of 117.65% over the size of Rs.6570.00 crores for the 8th Five Year Plan. Pursuant to the objectives and guidelines of the Planning Commission, the major thrust areas in the 9th Five Year Plan for the State of Punjab are:- Increased fillip to irrigation and power sectors, particularly through resource mobilisation out side the Annual Plan; Diversification of agricultural production and promotion of agro-processing and agro-based industries; Improvements in the quality of life, development of basic infrastructure , viz. provision of drinking water, roads etc. and quality based educational and health facilities.
Government of Punjab Department of Planning